Influence of moisture damage on fatigue cracking of asphalt binders, aggregate-binder interface, and mixtures - Silva, Lucas Sassaki Vieira da (2023)
The asphalt surface course in pavements is susceptible to several distresses, among of which there is fatigue cracking. Traffic and climate conditions during the pavement’s lifetime impact its behavior and might enhance the referred distress. The investigation in different scales of fatigue evolution under moisture effect is one of the verified gaps in the literature. Therefore, the objective of this research is to contribute to evaluate the effects of moisture induced damage on fatigue cracking on asphaltic materials in multiscale: binder, aggregate-binder interface, and asphalt mixtures. The used materials are gneiss aggregate, asphalt binder characterized by penetration as 50/70 and two adhesiveness promoters: an organic additive and Hydrated Lime. The methodology consists of dry and moisture-conditioned tests and computational simulation to predict cracking using two computational tools: CAP3D-D and FlexPAVETM. The following laboratory tests were performed: rheology (Frequency Sweep - FS and Linear Amplitude Sweep - LAS) for the binder; Asphalt Bond Strength (ABS) for the aggregate-binder interface; and uniaxial on asphalt mixtures (Dynamic Modulus - |E*| and Tensile-Compression Fatigue), in addition to Tensile Strength (TS) and Moisture-Induced Damage (MID) with the use of the Tensile Strength Ratio (TSR). The main conclusions are as follows: (i) no significant variations were observed for the binder scale, especially in the LAS test; (ii) the influence of pull-off rate and temperature on the aggregate-binder interface was confirmed by constructing a failure envelope. It is recommended to perform this test under conditions that closely resemble the actual field conditions; (iii) the asphalt mixture exhibited improved behavior in terms of MID when an organic additive and hydrated lime were used. The TSR values were found to be good indicators for the classification of |E*| and conditioned fatigue; (iv) computational simulation explicitly demonstrates the reduction of service life regarding fatigue cracking when moisture damage is taken into account; (v) fatigue tests performed without conditioning may overestimate the material's cracking resistance due to environmental conditions.